Diversity of bacterial isolates as biocontrol agents against Fusarium oxysporum f. sp. lycopersici - IRWANDHI IRWANDHI; NUR PRIHATININGSIH; SILVA ABRAHAM; MUHSON ISRONI; RIZKA GITAMI SATIVA; NADIA NURANIYA KAMALUDDIN; FIQRIAH HANUM KHUMAIRAH; HARIS MAULANA; EMMA TRINURANI SOFYAN; TUALAR SIMARMATA (Society for Indonesian Biodiversity, 2024)
Abstract. Irwandhi, Prihatiningsih N, Abraham S, Isroni M, Sativa RG, Kamaluddin NN, Khumairah FH, Maulana H, Sofyan ET, Simarmata T. 2024. Diversity of bacterial isolates as biocontrol agents against Fusarium oxysporum f. sp. lycopersici. Biodiversitas 25: 3403-3410. Fusarium oxysporum f. sp. lycopersici (FOL) is a soil-borne pathogen causing fusarium wilt in tomato plants, leading to significant crop losses worldwide. The severity of this disease is likely to increase with climate change, as rising temperatures and soil salinization create more favorable conditions for the pathogen. This study focused on characterizing bacterial isolates that could become biocontrol agents resilient to climate stress and identifying them through molecular techniques. Biochemical assays assessed the bacteria's ability to fix nitrogen and produce protease enzymes, siderophores, and hydrogen cyanide (HCN), which are essential for antagonizing FOL. The biological efficacy of these isolates was determined through antagonism assays, followed by molecular identification of the most effective isolates. A Completely Randomized Design (CRD) was used, involving six bacterial isolates and a control group with four replications for each treatment. All six isolates demonstrated the ability to fix nitrogen and produce protease enzymes, siderophores, and HCN, successfully inhibiting the growth of FOL. Among these, isolate R18 exhibited the strongest inhibition zone (55.55%), significantly reducing the mycelium weight to 0.0417 g, and showed tolerance to both temperature and salinity stress. Through 16S rRNA sequencing molecular identification, R11 was identified as Bacillus megaterium, and R18 was identified as Bacillus albus. These results highlight the potential of these bacterial isolates, especially R18, as effective biocontrol agents for managing fusarium wilt in tomato plants under changing climate conditions.